A rare case of fallopian tube lymphangioma - Doddareddy, Srikala; Manohar, Shravya; Manohar, Sumana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Lymphangioma of the fallopian tube is a very rare lesion, usually present as benign lesions of the lymphatic system. They are generally diagnosed incidentally, may be asymptomatic or present as a palpable abdominal mass. Lymphangiomas are usually seen in the head and neck region, intra-abdominal localisation is rare. A very limited number of cases of fallopian tube lymphangiomas have been reported. We present an extremely rare case of unilateral fallopian tube lymphangioma (right side) in a 32 year old parous lady who was presented to us with right lower abdominal pain. Clinically no significant findings were noted. CECT abdomen reported as a probable endometriotic cyst. On laparoscopy she was found to have a cystic lesion arising from the right fallopian tube. Patient underwent right salphingo-oophorectomy and histopathology reported as lymphangioma of the fallopian tube.